Financial Motivation Undermines Maintenance in an Intensive Diet and Activity Intervention - Arlen C. Moller; H. Gene McFadden; Donald Hedeker; Bonnie Spring (Hindawi Limited, 2012)
Financial incentives are widely used in health behavior interventions. However, self-determination theory posits that emphasizing financial incentives can have negative consequences if experienced as controlling. Feeling controlled into performing a behavior tends to reduce enjoyment and undermine maintenance after financial contingencies are removed (the undermining effect). We assessed participants' context-specific financial motivation to participate in the Make Better Choices trial-a trial testing four different strategies for improving four health risk behaviors: low fruit and vegetable intake, high saturated fat intake, low physical activity, and high sedentary screen time. The primary outcome was overall healthy lifestyle change; weight loss was a secondary outcome. Financial incentives were contingent upon meeting behavior goals for 3 weeks and became contingent upon merely providing data during the 4.5-month maintenance period. Financial motivation for participation was assessed at baseline using a 7-item scale (𝛼=.97). Across conditions, a main effect of financial motivation predicted a steeper rate of weight regained during the maintenance period, 𝑡(165)=2.15, 𝑃=.04. Furthermore, financial motivation and gender interacted significantly in predicting maintenance of healthy diet and activity changes, 𝑡(160)=2.42, 𝑃=.016, such that financial motivation had a more deleterious influence among men. Implications for practice and future research on incentivized lifestyle and weight interventions are discussed.